2018
DOI: 10.1080/15438627.2018.1550401
|View full text |Cite
|
Sign up to set email alerts
|

Applications of omega-3 polyunsaturated fatty acid supplementation for sport performance

Abstract: Omega-3 (n-3) polyunsaturated fatty acid (PUFA) supplementation has recently been proposed as an ergogenic aid for athletes. This claim is primarily based on mechanistic evidence that n-3PUFA's exert anti-inflammatory properties and act to change the functional capacity of the muscle cell by modifying the membrane fluidity of proteins and lipids within the cell membrane. In this review, we critically evaluate the scientific literature that examines the efficacy of n-3PUFA supplementation to improve athlete per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 82 publications
1
56
0
Order By: Relevance
“…In the present study, we found this outcome with a shorter supplementation time (4 weeks). One explanation can be that our product was richer in DHA while the previous trial employed primarily EPA, which requires transformation to DHA by the enzyme omega-3 desaturase (which adds the additional double bond required to the C15) which showed variability in its conversion to DHA in previous clinical trials [48]. Previous studies found that DHA incorporation to other tissues is paralleled by incorporation of DHA to erythrocyte tissues [49,50], thus we assumed that the product employed effectively reached target tissues to exert antioxidant properties.…”
Section: Secondary Finding: Dha Is Incorporated To Erythrocytes Dose-mentioning
confidence: 99%
“…In the present study, we found this outcome with a shorter supplementation time (4 weeks). One explanation can be that our product was richer in DHA while the previous trial employed primarily EPA, which requires transformation to DHA by the enzyme omega-3 desaturase (which adds the additional double bond required to the C15) which showed variability in its conversion to DHA in previous clinical trials [48]. Previous studies found that DHA incorporation to other tissues is paralleled by incorporation of DHA to erythrocyte tissues [49,50], thus we assumed that the product employed effectively reached target tissues to exert antioxidant properties.…”
Section: Secondary Finding: Dha Is Incorporated To Erythrocytes Dose-mentioning
confidence: 99%
“…Furthermore, n-3 PUFAs can modify the membrane fluidity of proteins and lipids within the cell membrane, reducing oxygen consumption and thus improving endurance capacity (Philpott et al, 2019). Different studies on healthy animals (for example birds – semipalmated sandpipers Calidris pusilla or rats) showed that n-3 PUFA supplementation supports recovery of muscle damage caused by exercise and changes muscle lipid composition (Ayre and Hulbert, 1997; Ruf et al, 2006; Maillet and Weber, 2007; Nagahuedi et al, 2009).…”
Section: N-3 Pufas Enhance Endurance Capacity During Exercise In Animmentioning
confidence: 99%
“…Linday et al (98) found that the simultaneous administration of cod liver oil (which contains EPA and vitamin A) and a multivitamin-mineral supplement to children led to a statistically significant (P<0.05) decrease in the mean number of URTI-related medical consultations over time. Overall, omega-3 fatty acids confer significant health benefits to patients with URTI complications and shorten the length of stay of acutely ill patients in hospital (99)(100)(101). Since omega-3 fatty acids have proven to be effective in reducing airway inflammation and bronchoconstriction, have also exhibited efficacy against viral infections (102,103), their potential for use against COVID-19 warrants further investigation (104)(105)(106).…”
Section: Amino Acidsmentioning
confidence: 99%